2a + 2/3 = a - 1/3
subtract a from both sides to get:
a + 2/3 = -1/3
subtract 2/3 from both sides to get:
a = -1
.
2006-10-30 11:44:33
·
answer #1
·
answered by djc 3
·
0⤊
0⤋
2a + 2/3 = a - 1/3
-2/3 = -2/3
2a = a - 1
-a = -a
a = -1
2006-10-30 19:47:07
·
answer #2
·
answered by Peter 3
·
0⤊
0⤋
2a + 2/3 = a - 1/3
2a-a=-1/3-2/3
a=-1
2006-10-30 19:56:16
·
answer #3
·
answered by yupchagee 7
·
0⤊
0⤋
first we can add -a(minus a) to both sides of the equation
then we get
2a+2/3+(-a)=a-1/3+(-a)
so 2a+(-a)+2/3=a+(-a)-1/3
2a-a+2/3=a-a-1/3
a+2/3=-1/3
when we add -2/3 at both sides,
we will get a+2/3 +(-2/3)=-1/3+(-2/3)
so a=-1/3-2/3=-1 a=-1 is the correct answer
2006-10-30 19:53:49
·
answer #4
·
answered by peterwan1982 2
·
0⤊
0⤋
2a + 2/3 = a - 1/3
-a ````````` -a
a + 2/3 = -1/3
-2/3 ``````-2/3
a = -3/3
a = -1
2006-10-30 19:47:41
·
answer #5
·
answered by smiley 3
·
0⤊
0⤋
2a + 2/3 = a - 1/3
2a + 3/3 = 1
2a = 1-3
2a=-2
a=-1
2006-10-30 19:46:29
·
answer #6
·
answered by Lewis M 3
·
0⤊
0⤋
You want to get the a's all on one side by themselves:
2a = a -1/3 - 2/3
2a - a = -1
a = -1
2006-10-30 19:45:16
·
answer #7
·
answered by The Pulverizer 4
·
0⤊
1⤋